Host-Feeding Sources and Infection With Trypanosoma cruzi of Triatoma infestans and Triatoma eratyrusiformis (Hemiptera: Reduviidae) From the Calchaqui Valleys in Northwestern Argentina - Fernandez, M.P. (2020)
Fil: Fernandez, M.P. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.